Improving Students’ Application of Moment of Force Concepts in Physics through Experimental Approach, a case of Secondary Schools in Marakwet West Sub-County, Elgeyo Marakwet County, Kenya - Chepkwony, Samuel K.; Ronno , Cosmas; Samikwo , Dinah C. (African Journal of Education,Science and Technology (AJEST), 2021)
An investigation was carried out to ascertain the effectiveness of experimental approach on students’ application of moment of force concepts in Physics in secondary schools in Marakwet West Sub-county, Elgeyo Marakwet County, Kenya. This investigation was informed by the reviewed literature which showed that students are not able to apply moment of force concepts to solve moment of force problems in physics examination due to predominant lecture method of teaching used in physics lessons. The study was carried out in seven selected secondary schools in Marakwet West Sub-county, where students have persistently scored low grades in the subject. The objective was therefore, to investigate the effect of this approach on students’ application of moment of force concepts. In the investigation, a quasi-experimental nonequivalent group design was used. Stratified sampling was used to cluster schools into four strata. Simple random sampling technique was used to select two schools from each stratum. Simple random sampling was further used in placing the selected schools into either experimental or control group. Data was collected from a sample of 271 students sampled from 1500 target population. Tests on moment of force were used as vital instruments for collecting data. The data obtained was analyzed using t-independent tests with the aid of SPSS. The findings showed that students taught through experimental approach performed better in retention and application tests in posttest as compared to those students taught through lecture method. From the findings, it was recommended that all schools laboratories should be equipped with teaching/learning materials as well as improvisation of these materials whenever they are inadequate for moment of force concepts to taught experimentally. These results will be useful to Physics teachers, curriculum developers (KICD), and policy makers.